News Framing of the Rohingya Crisis Settlement: a Study on Aljazeera and BBC: Osama Kanaker, Mohamed Oklah Abughazlih, Mohamed Battour, Ihab Ahmed Awais, Khalaf Mohammed Tahat (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
This study aims to discover how Aljazeera and BBC TV channels framed the Rohingya crisis settlements that were spent by national and international bodies. The content analysis was implemented by following mixed method approach. The results were obtained from the qualitative analysis of Aljazeera and BBC news, as well as the statistical quantitative results. The findings showed that news framing is capable of shaping certain attitudes toward incidents. Three main frames were utilized in the news coverage of Aljazeera and BBC: responsibility, human impact, and powerlessness frames. The findings are valuable to news organizations and reporters in framing minority crisis news. It may also assist audiences to critically understand the frames that shaped the crisis settlement news, and thereby enable them to further understand how media frame incidents and conflicts.
Keywords: News; Framing; Rohingya Crisis; Settlement; Aljazeera; BBC.